Penerapan Media Pembelajaran Mystery Box Untuk Meningkatkan Motivasi Dan Hasil Belajar Siswa Kelas IV Pada Mata Pelajaran PPKN Di SD Negeri 8 Tamasongo Kabupaten Takalar - Sri Windayanti; Muhajir Muhajir; Rismawati Rismawati (International Forum of Researchers and Lecturers, 2024)
This research aims to determine the application of the Mystery Box learning media to increase the motivation and learning outcomes of class IV students in Civics subjects at SD Negeri 8 Tamasongo, Takalar Regency. This research uses the classroom action research (PTK) method which consists of two cycles where each cycle is carried out in four meetings. The subjects of this research were fourth grade students at SD Negeri 8 Tamasongo, Takalar Regency. The research instruments are observation sheets, tests and documentation. The data collection technique uses tests, observation and documentation. The results of the research show that the motivation and learning outcomes of class IV students at SD Negeri 8 Tamasongo, Takalar Regency in the PPKn subject in cycle I obtained an average student learning outcome score of 62.5, where only 4 students out of 10 students completed or 40% and It can also be seen from the results of observing student motivation that there were 2 students who experienced an increase in motivation, while in cycle II the average value of student learning outcomes was 84.5, where 8 or 80% of students completed it and it can also be seen from the results of observing student motivation. 9 students experienced an increase in motivation. Based on the results of the research above, it can be concluded that the application of the Mystery Box learning media can increase the motivation and learning outcomes of class IV students in Civics subjects at SD Negeri 8 Tamasongo, Takalar Regency.